Activation of TRPV4 channels leads to a consistent tocolytic effect on human myometrial tissues. (April 2021) - Villegas, Daniela; Giard, Olivier; Brochu-Gaudreau, Karine; Rousseau, Éric
Highlights: Specific pharmacological activation of alternative Ca 2+ conductance. Activation of TRPV channels, abolishes the rhythmic contractile activity. Tocolysis was consistently induced on human myometrial strips. Abstract: Background: Human myometrium is a therapeutic target for labor induction and preterm labor. Objective: This study aimed to assess the physiological role of alternative calcium conductance on contractions triggered by uterotonic drugs in human myometrium. Membrane conductances, supported by TRPV channels, may provide alternative pathways to control either free intracellular and/or submembrane Ca 2+ -concentration, which in turn will modulate membrane polarization and contractile responses. Study design: Uterine biopsies were obtained from consenting women undergoing elective caesarean delivery at term without labor (N = 22). Isometric tension measurements were performed on uterine smooth muscle strips (n = 132). Amplitude, frequency, and area under the curve (AUC) of phasic contractions, as well as resting tone, were measured under various experimental conditions. Immuno histo- and cyto-chemistry, as well as Western blot analyses, have been performed with specific antibodies against TRPV1, TRPV3, and TRPV4 proteins. TRPV4 agonists; GSK1016790A, 4αPDD, and 5, 6-EET were used to assess the role of TRPV4 channels on rhythmic activity triggered by 30–300 nM oxytocin. 5 μM of ruthenium red was used as an efficient blocker of ionic current through TRPV4 channels. Nanomolar concentrations of iberiotoxin (IbTX) were also used to confirm the downstream involvement of BKCa channels in controlling uterine reactivity and contractility. Results: The expression of TRPV3 and TRPV4 isoforms has now been demonstrated in human myometrial tissue and cell culture. Nanomolar concentrations of the TRPV4 agonists, (either GSK1016790A or 4αPDD) abolished the rhythmic contractions, resulting in a rapid and consistent tocolytic effect. While 5 μM of ruthenium reversed this tocolytic effect. The addition of IbTX (a BKCa channel blocker) reversed the effects of GSK1016790A. Carvacrol, a TRPV3 agonist, had similar tocolytic effects on rhythmic contractions albeit at higher concentrations. This inhibitory effect was also reversed by ruthenium red. Conclusion: Collectively, these data suggest that activation of TRPV4 leads to a Ca 2+ entry and subsequent BKCa channel activation (increase in open state probability), which in turn hyperpolarizes the myometrial cell membrane, inactivating L-type Ca 2+ channels and efficiently abrogates contractile activity. Consequently, alternative Ca 2+ conductance supported by TRPV4 plays a physiological role in the modulation of myometrial reactivity.